Comparative Effectiveness of Duloxetine and Pelvic Floor Exercises for Stress Urinary Incontinence in Postmenopausal Women: A Quasi-Experimental Study in a Secondary Care Setting, Islamabad: Exercises for Stress Urinary Incontinence - Rubab, Asia; Inam, Ayesha; Ayub, Afsah; Raza, Amna (Pakistan Journal of Health Sciences, 2025)
Stress urinary incontinence has great impact on female daily activities, emotional well-being, and overall quality of life; hence the need of most effective treatment is mandatory. Objective: To evaluate the effectiveness of Duloxetine and Pelvic Floor Muscle Training (PFMT) in the management of Stress Urinary Incontinence (SUI) in postmenopausal women. This study also aims to estimate symptom reduction, adherence rates, quality of life, and associated factors. Methods: Sample consist of 100 participants who were randomly assigned to two groups: Duloxetine (n=50) and PFMT (n=50). Reduction in weekly incontinence episodes over the period of 12 weeks was considered as the primary outcome. Improvement in quality of life, adherence rates, strengthening pelvic floor muscle and reduction in adverse effects was considered as the secondary outcome. Results: A considerable reduction in the weekly incontinence episodes was seen in both groups and no statistically significant difference (p = 0.08) was found among two groups. Similarly, quality of life scores was also improved significantly (p < 0.001), post intervention with PFMT group exhibiting a marginal advantage. Only the PFMT group exhibited significant pelvic floor muscle strengthening (p < 0.001). Mild adverse effects, including nausea and fatigue, were reported in 12% of participants in the Duloxetine group, while PFMT had no reported side effects. Conclusions: Both Duloxetine and PFMT effectively reduced SUI symptoms and improved quality of life. However, PFMT had advantages in adherence, safety, and pelvic floor muscle strengthening, making it the preferred first-line treatment.